The Relationship Between Academic Self-Efficacy and Learning Motivation Among Junior High School Students - Mahdav Viqiyan Sirlani; Hema Dayita; Andreas Corsini Widya Nugraha (Socrates: Journal of Education, Philosophy and Psychology, 2026)
This research is prompted by the phenomenon of low learning motivation and low academic self-efficacy among students in facing academic demands, as well as deviant behaviors in school. This study aims to determine the relationship between academic self-efficacy and learning motivation among junior high school students. The method used in this research is a correlational quantitative approach. The research sample consisted of 59 active students at SMP Bhineka Tunggal Ika, obtained using the total sampling technique. The instruments used were the Academic Self-Efficacy Scale (ASES) and the Academic Motivation Scale (AMS). The results indicated that the majority of students possessed high levels of academic self-efficacy (71.19%) and learning motivation (74.58%). Hypothesis testing confirms a significant positive linear relationship between academic self-efficacy and learning motivation in junior high school students. In conclusion, there is a highly significant positive relationship between academic self-efficacy and learning motivation among junior high school students, proving that these two psychological dynamics are closely intertwined rather than independent.